Spinal abscess after epidural block and radiofrequency ablation in a patient with post-herpetic neuralgia - Jiang Qun; Zeng Ting; Guo Lingsong; Zhang Guangiang (Journal of the Pakistan Medical Association, 2023)
A 67-year-old man was admitted due to a two-week history of pain on the right side of his chest, upper back, and armpit, and progressive lower-limb weakness. The results of Magnetic Resonance Imaging and colour ultrasound supported the diagnosis of spinal abscess. The patient underwent a series of debridement and antibacterial treatments, but no obvious recovery of muscle strength was observed. This case highlights the potentially serious complications of invasive analgesic therapy. Keywords: Case report, Epidural block, Spinal abscess, Post-herpetic neuralgia, Radiofrequency ablation.